Global burden of lung cancer in adolescents and adults aged 15–45: analysis of the global burden of disease study (1990–2021) - Ziqi Han; Zhigang Zhu; Zhiqiang Zhang; Jiayang Dong; Xinyue Yang; Jing Feng (Frontiers in Medicine)
BackgroundLung cancer is a leading cause of cancer-related deaths around the world, but its impact on young and middle-aged individuals (aged 15–45 years) is less understood. The aim of this study was to assess the global burden of lung cancer in those aged 15–45 years during 1990–2021.MethodsThis study estimated global trends in prevalence, mortality, and disability-adjusted life years (DALYs) associated with lung cancer in this age group. The Global Burden of Disease Study 2021 was utilized to analyze data from 1990 to 2021. We examined variations by sex, age subgroup, sociodemographic index (SDI), and region and assessed key risk factors contributing to DALYs.ResultsOur findings reveal that while the number of lung cancer cases aged 15–45 increased by 22.1%, the age-standardized prevalence decreased by 23.9%; age-standardized mortality and DALYs declined significantly over the past three decades. The decrease was more evident among men than women, despite men having a higher overall disease burden. In high-SDI countries, prevalence and DALYs experienced substantial decreases, whereas low-SDI countries experienced increases, particularly among women. East Asia demonstrated a high disease burden. Smoking was identified as the most prominent risk factor, especially in high-middle SDI countries. Household air pollution and ambient particulate matter pollution came after it.ConclusionThe study underscores the effectiveness of tobacco control measures and early screening in reducing lung cancer burden among young and middle-aged individuals. Nevertheless, the upward trends in low - SDI countries emphasize the necessity for interventions that are specifically aimed at environmental risk factors and smoking cessation initiatives. These findings provide valuable insights for policymakers and healthcare providers aiming to implement strategies to further cut down the global burden of lung cancer in the younger population.